Organising the Digitisation of Collections at a National or International Level: Models for Research Library Development - Renoult, Daniel (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
Libraries today, amongst other research institutions, are solicited more and more to take part in programmes of digitisation of their collections. Apart from the way these programmes affect the public image of the institution and the prestige that is to be gained, participating in these programmes leads us to consider not only technical decisions but above all long term strategic choices.